Pelatihan Penyusunan Instrumen Asesmen Numerasi Berbasis Higher Order Thinking Skills (HOTS) Untuk Siswa Kelas Awal - Bhoke, Wilibaldus; Wea, Marselina (PELITA NUSA TENGGARA, 2025)
Assessment is an essential aspect of the learning process, especially at the early elementary school level. In line with the implementation of the Minimum Competency Assessment (AKM), teachers are required to be able to design contextual numeracy assessment instruments that align with students’ cognitive development and integrate HOTS-based approaches as well as local cultural elements. This study aims to describe the process and outcomes of mentoring programs in developing numeracy assessment instruments for early grade elementary school teachers. The method used is qualitative with a literature review approach, supported by findings from various previous mentoring practices. The results show that mentoring through workshops, simulations, gamification, and the use of digital technology can enhance teachers’ ability to create valid, contextual, and formative-aligned numeracy assessment items. Teachers also demonstrated increased understanding of numeracy literacy concepts and were able to produce instruments suitable for both diagnostic and summative assessments. Collaborative and participatory mentoring further strengthened teacher confidence and fostered the formation of professional learning communities. Mentoring is proven to be highly effective in improving the quality of numeracy assessment at the elementary level, both in terms of technical aspects of item development and pedagogical approaches used. It is recommended that mentoring be carried out continuously, with support from educational institutions and competent facilitators, and extended to other literacy domains. In this way, teachers can optimally contribute to achieving the goals of the Pancasila Student Profile and promoting more equitable quality basic education.